2016
DOI: 10.1074/jbc.m116.721084
|View full text |Cite
|
Sign up to set email alerts
|

Do Src Kinase and Caveolin Interact Directly with Na,K-ATPase?

Abstract: Much evidence points to a role of Na,K-ATPase in ouabaindependent signal transduction. Based on experiments with different cell lines and native tissue membranes, a current hypothesis postulates direct interactions between the Na,K-ATPase and Src kinase (non-receptor tyrosine kinase). Na,K-ATPase is proposed to bind Src kinase and inhibit its activity, whereas ouabain, the specific Na,K-ATPase inhibitor, binds and stabilizes the E2 conformation, thus exposing the Src kinase domain and its active site Tyr-418 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 48 publications
1
38
1
1
Order By: Relevance
“…There is substantial evidence for physical interaction between the Na + ,K + -ATPase and Src that is disturbed by ouabain but does not depend on ATPase activity (for details, see Cui & Xie, 2017). This is in disagreement with cell-free assay-based studies, which suggested that Src is activated by changes in ATP consumption (Yosef, Katz, Peleg, Mehlman, & Karlish, 2016).…”
Section: Ion-transport-independent Signal Transductionmentioning
confidence: 99%
“…There is substantial evidence for physical interaction between the Na + ,K + -ATPase and Src that is disturbed by ouabain but does not depend on ATPase activity (for details, see Cui & Xie, 2017). This is in disagreement with cell-free assay-based studies, which suggested that Src is activated by changes in ATP consumption (Yosef, Katz, Peleg, Mehlman, & Karlish, 2016).…”
Section: Ion-transport-independent Signal Transductionmentioning
confidence: 99%
“…A second model is that c-Src activation is primarily a consequence of an ATP-sparing effect (observed in a cell-free system) [45, 46]. A third model proposes that c-Src transiently interacts with a complex formed between the Na/K-ATPase α1 subunit and caveolin-1[47]. A common charateristic in these models is that the E2-P conformational state of the Na/K-ATPase is favored, and stablized by Na/K- ATPase inhibitors (ouabain, vanadate, oligomycin) and energy status (ATP/ADP ratio).…”
Section: The Na/k-atpase: Ion Pumping and Signaling Functionmentioning
confidence: 99%
“…There are some data that are opposite with our model. It has been shown that c-Src activation was not involved in ouabain induced Na/K-ATPase endocytosis in non-small cell lung cancer cells [86] and no stable interactions were detected between purified recombinant Na/K-ATPase and purified human Src kinase [87]. We would like to point out that these observations are different from what we have reported using purified pig kidney Na/K-ATPase, LLC-PK1 cell, human HK-2, human dermal fibroblasts, renal fibroblast cell line, and rat cardiac fibroblasts cell line [84,88,89].…”
Section: Na/k-atpase – An Ion Pump a Signaling Receptor And A Sigmentioning
confidence: 99%